Автоматизація потокових ліній і роботизованих комплексів у виробництві кондитерських виробів - Дмитревський, Дмитро В’ячеславович; Загорулько, Олексій Євгенович; Dmytrevskyi, Dmytro; Zagorulko, Aleksey (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто актуальні питання автоматизації потокових ліній кондитерського виробництва через інтеграцію інтелектуальних роботизованих комплексів. Обґрунтовано необхідність переходу від жорстких автоматизованих систем до гнучких кіберфізичних структур у межах концепції Індустрії 4.0. Основну увагу приділено застосуванню дельта-роботів, оснащених системами технічного зору й алгоритмами глибокого машинного навчання, що дає змогу забезпечити делікатне поводження з крихкою продукцією та здійснювати контроль якості в реальному часі. Описано принципи адаптивного керування технологічними параметрами, які дають змогу стабілізувати реологічні властивості кондитерських мас. Результати дослідження підтверджують, що впровадження запропонованих рішень підвищує продуктивність ліній, мінімізує частку браку та значно скорочує час переналагодження обладнання при зміні асортименту продукції. /// EN: The article deals with the complex problems of automating production lines and integrating robotic systems within the modern confectionery manufacturing sector. Confectionery production is characterized by highspeed technological processes, sensitive raw materials, and strict requirements for product aesthetics. Traditional automation often lacks the flexibility required to adapt to rapidly changing consumer demands and the diverse physical properties of products such as chocolates, biscuits, and delicate pastries. The study is based on the principles of the Industry 4.0 concept, focusing on the transition from rigid mechanical automation to flexible cyber-physical systems. The research investigates the application of parallel kinematics, specifically delta robots, synchronized with high-speed conveyor belts. A significant part of the work is dedicated to the implementation of artificial intelligence, specifically deep learning neural networks, into computer vision systems to ensure real-time quality inspection and object orientation detection. The author proposes a hierarchical control architecture that integrates programmable logic controllers with robotic cells through real-time industrial communication protocols. The research demonstrates that the use of adaptive soft grippers and force-sensing technologies allows robotic complexes to handle fragile items without compromising their structural integrity. Furthermore, the implementation of recipe-based management systems significantly reduces downtime during product changeovers. The study also addresses the issues of energy efficiency and predictive maintenance, showing that digital twin modeling can optimize the energy consumption of robotic arm trajectories. The findings confirm that the integration of intelligent robotics into confectionery streamlines leads to a synergistic effect, enhancing both productivity and product quality. The proposed automation framework minimizes the impact of human error, ensures total quality control, and provides the necessary flexibility for smallbatch production. This research provides a theoretical and practical basis for the technological modernization of food industry enterprises aiming to improve their global competitiveness in the digital age.
Automation of production lines and robotic systems in confectionery manufacturing
Keywords: автоматизація; кондитерська промисловість; потокові лінії; роботизовані комплекси; про- мислові роботи; системи керування; технологічний процес; automation; confectionery industry; production lines; robotic systems; industrial robots; control systems; technological process